2007
DOI: 10.1016/j.jdeveco.2005.08.003
|View full text |Cite
|
Sign up to set email alerts
|

How transition paths differ: Enterprise performance in Russia and China

Abstract: We use enterprise survey data to analyse and contrast the determinants of enterprise performance in China and Russia. We find that in China, enterprise growth and efficiency is associated with rapid increases in factor inputs, and with ownership to a lesser extent, but not greatly correlated with industry-specific or institutional factors. However, in Russia, enterprise growth is not associated with improvements in factor quantity (except for labor) or quality. The main determinants of company performance are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…In Table 2, therefore, we report the distributions of the aforementioned estimates. 4 The coefficient estimates suggest that the returns to scale for the median firm is 1.00, which is consistent with our expectations about returns to scale of mature industries. The estimates also indicate that the median marginal contribution of capital to the output firm is less than those of labor and material inputs, which is consistent with selective evidence about significant investment in physical capital -specifically, power looms -in textiles industries in developing countries (Bhaumik et al, 2008).…”
Section: Regression Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In Table 2, therefore, we report the distributions of the aforementioned estimates. 4 The coefficient estimates suggest that the returns to scale for the median firm is 1.00, which is consistent with our expectations about returns to scale of mature industries. The estimates also indicate that the median marginal contribution of capital to the output firm is less than those of labor and material inputs, which is consistent with selective evidence about significant investment in physical capital -specifically, power looms -in textiles industries in developing countries (Bhaumik et al, 2008).…”
Section: Regression Resultssupporting
confidence: 86%
“…Bhaumik and Estrin (2007), for example, model output (or sales) as a function of firm-specific characteristics such as factor inputs and ownership, as well as institutional (and economic) characteristics of the regions in which the firms are located. In other words, output of the i th firm is given by…”
Section: Stylized Modeling Approachmentioning
confidence: 99%
“…For instance, the inconsistency of legal and regulative environment in Russia resulted in the state's attempts to help SMEs, and to capture their profits and resources at the same time (Frye and Shleifer 1997;Zhuplev, Kon'kov, and Kiesner 1998). In Russia, firm growth and performance are associated with institutional factors and with the state of regional institutional arrangements (Bhaumik and Estrin 2007).…”
Section: Entrepreneurship and Smes In Changing Institutional Settingsmentioning
confidence: 99%
“…As for the industrial economies, the impact on China's economic growth from the perspective of the factors of the three major industries was studied by some scholars (Fan et al, 2003;Bhaumik et al, 2007;Gong et al, 2008). Bai (2014) analyse the labor twisted configuration on social outcomes in the three major industries and the research shown that the first and tertiary industry configured the number of labor over the amount of labor in the twisted state and the second industry take the opposite effect.…”
Section: Introductionmentioning
confidence: 99%